Effect of the solvent on the morphology of sulfamerazine crystals and its molecular mechanism. Issue 30 (14th July 2022) - Li, Liang; Ji, Xiongtao; Cheng, Xiaowei; Li, Danning; Wang, Ting; Huang, Xin; Wang, Na; Yin, Qiuxiang; Hao, Hongxun
Abstract : To have a better understanding on molecular mechanism of crystal morphology manipulation, the effect of the solvent is investigated using different solvents. Abstract : To have a better understanding on the molecular mechanism of the crystal morphology manipulation, the effect of the solvent on the morphology of crystals was investigated using sulfamerazine (SMR) as a model compound and through a combination of experimental investigations and molecular simulations. The modified attachment energy model was employed to build the crystal morphology model in different solvents. Hirshfeld surfaces and 2D fingerprint plots were used to investigate the solute–solute interactions, and molecular dynamics simulation was employed to investigate the interactions between solvent molecules and different crystal faces. The functions of factors such as the surface structure, roughness, and the radial distribution were also considered and discussed. The results suggested that these factors are important to the crystal habits, since they could affect the adsorption competition between the solute and solvent molecules. It was found that the method developed in this work could be used to predict the morphology of SMR and could guide the selection of crystallization solvents for obtaining target morphology.